2008
DOI: 10.1021/ol802329y
|View full text |Cite
|
Sign up to set email alerts
|

Formal Synthesis of (±)-Roseophilin

Abstract: A formal synthesis of (±)-roseophilin is described. Scandium(III)-catalyzed Nazarov cyclization of 2,5-disubstituted N-tosylpyrrole 19 gives a 5,5'-fused ketopyrrole, and ansa-bridge formation via π-allyl palladium macrocyclization gives 21.Roseophilin (1), isolated from Streptomyces griseoviridis, was identified as a potent cytotoxic agent against K562 human erythroid leukemia cells (chronic myeloid leukemia model; IC 50 , 0.34 μM) and KB human epidermoid carcinoma cells (nasopharyngeal carcinoma model; IC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Later, it was revealed that these 2-substituted furyl and benzofuryl Nazarov precursors undergo a fundamentally different reaction that involves a 1,2-hydride migration and Friedel-Crafts alkylation catalyzed by tricationic iridium(III). [13] The Nazarov cyclization of dienones containing N, O, or S heterocyclic moieties (198) was described by Occhiato and coworkers to occur most efficiently with metal triflates such as Sc(OTf) 3 or In(OTf) 3 (3-15 mol %; Scheme 39). [13] The Nazarov cyclization of dienones containing N, O, or S heterocyclic moieties (198) was described by Occhiato and coworkers to occur most efficiently with metal triflates such as Sc(OTf) 3 or In(OTf) 3 (3-15 mol %; Scheme 39).…”
Section: Sc(otf) 3 or In(otf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Later, it was revealed that these 2-substituted furyl and benzofuryl Nazarov precursors undergo a fundamentally different reaction that involves a 1,2-hydride migration and Friedel-Crafts alkylation catalyzed by tricationic iridium(III). [13] The Nazarov cyclization of dienones containing N, O, or S heterocyclic moieties (198) was described by Occhiato and coworkers to occur most efficiently with metal triflates such as Sc(OTf) 3 or In(OTf) 3 (3-15 mol %; Scheme 39). [13] The Nazarov cyclization of dienones containing N, O, or S heterocyclic moieties (198) was described by Occhiato and coworkers to occur most efficiently with metal triflates such as Sc(OTf) 3 or In(OTf) 3 (3-15 mol %; Scheme 39).…”
Section: Sc(otf) 3 or In(otf)mentioning
confidence: 99%
“…[115] In 2009, Frontier and Bitar reported the formal synthesis of a potent cytotoxic agent, roseophilin (197), that utilizes the Sc(OTf) 3 /LiClO 4 method for the key step, a Nazarov cyclization of a 2,5-disubstituted N-tosylpyrrole intermediate (195) to give 196 in 65 % yield (Scheme 38). [13] The Nazarov cyclization of dienones containing N, O, or S heterocyclic moieties (198) was described by Occhiato and coworkers to occur most efficiently with metal triflates such as Sc(OTf) 3 or In(OTf) 3 (3-15 mol %; Scheme 39). [116,117] Copper(II) triflate had comparable activity for N-heterocyclic substrates.…”
Section: Sc(otf) 3 or In(otf)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In electronic polarization of the Nazarov substrate, one of the vinyl groups is made electrophilic and the other nucleophilic ( A in Scheme 1) so that the reaction proceeds more readily and under catalytic conditions with mild Lewis acids such as Cu(OTf) 2 3 Furthermore, the charge asymmetry that is produced in oxyallyl cation B by the electron-donating and -withdrawing groups results in regioselective elimination. Recent studies describe the use of Cu(II), 3,4 Pd(II), 5 Sc(III), 6 Ir(III), 7 V(IV), 8 Ni(II), 9 Au(I), 10 Fe(II) 11 or Co(I) 11 complexes in sub-stoichiometric amounts for catalysis of the Nazarov cyclization, including several chiral complexes furnishing cyclopentenones with modest to high enantiometric excesses. Several methodologies based on organocatalysis have also emerged to deliver Nazarov products with good enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrrolyl vinyl ketone 160 (Scheme 37), prepared by oxidation of the 4-isoxazoline 159, underwent Nazarov cyclization to give the 5,5Ј-fused keto pyrrole 161. π-Allyl palladium macrocyclization afforded 162, which can be converted into the target molecule. [66] The proline-derived bicyclic 4-isoxazolines 163 (Scheme 38), each bearing a carboxylic substituent at C-3, afford the acyclic nitrosoalkyl-substituted α,β-unsaturated ketones 165 upon treatment with mCPBA. [67] Reduction of 4-isoxazoles can lead to β-amino ketones or β-amino alcohols.…”
Section: -Isoxazolines As Building Blocks For Acyclic Compoundsmentioning
confidence: 99%